Impact of infill pattern and infill density on mechanical properties of FDM 3D printed parts: a review - Abdellah El omari; Aissa Ouballouch; Mohammed Nassraoui (Incertitudes et Fiabilité des Systèmes Multiphysiques)
Fused Deposition Modeling (FDM) process is widely used for various applications as it offers many benefits. Mechanical properties of parts manufactured using FDM technique are very critical. For that reason, it is important to understand how different values of process parameters affect these properties. The purpose of this research is to provide information related to the influence of various infill pattern and infill density. A literature review is carried out based on the current researches that investigate FDM 3D printing process of polymer materials. The results show that infill percentage then layer thickness are the most influential process parameter on most of the material’s mechanical properties. In addition, this work identifies gaps in existing studies and highlights opportunities for future research.